ICC at 25: The Outer Rims of Jurisdiction - Ádány, Tamás (The ICC at 25: Lessons Learnt, 2025)
Since its establishment in 2002, the International Criminal Court (ICC) has clarified key jurisdictional issues arising from the Rome Statute and the UN Charter, emphasizing personal, territorial, and temporal jurisdiction. After twenty-five years, the ICC faces criticism for limited effectiveness and accusations of bias, yet it endures and has made significant progress. Its jurisprudence reflects a cautious adherence to international law, enhancing legal certainty despite challenges in a fragmented system. However, state withdrawals and lack of cooperation threaten investigations and prosecutions, complicating the Court’s retributive function. Nonetheless, the ICC’s patience and the political stigma of indictments serve preventive goals by deterring future crimes. Despite ongoing difficulties, the Court’s experience offers cautious optimism for international criminal justice and accountability. Keywords: International Criminal Court (ICC), jurisdiction, Rome Statute, international criminal justice, legal effectiveness